The Effect of Self-Regulated Learning Training on Student Academic Procrastination Behavior - Gillberth Cornelis Benjamin Saudale; Mariana Dinah Ch Lerik; Dian Lestari Anakaka (Universitas Nusa Cendana, 2023)
Students have responsibilities as students of knowledge and complete academic tasks. The assignments given can help students to improve their understanding of the material presented. One of the problems that can be experienced by students related to academic assignments is that students often delay doing assignments in an academic context or what is known as academic procrastination. Academic procrastination is thought to be the result of a failure of self-regulation that adversely affects the well-being and academic performance of students. This problem was also found in students of the Psychology Study Program, Faculty of Public Health, Nusa Cendana University class 2017. One thing that can be done to overcome this problem is to provide Self-Regulated Learning training to students who often delay their academic assignments. This research was conducted to see the effect of Self-Regulated Learning training to reduce the level of academic procrastination behavior among students. This type of research is Quasi Experimental research. Participants in this study amounted to 13 students who have met the research requirements. The results of the analysis of research data indicate that Self-Regulated Learning training has an effect on reducing student academic procrastination behavior.